In-situ observation of damage mechanisms by digital image correlation during tension and low cycle fatigue of magnesium alloys - Khan, A; Marrow, T (2009)
A full field strain mapping technique based on digital image correlation analysis has been used to observe the surface strain fields during tensile and low cycle fatigue deformation of magnesium alloys Elektron WE43 and Elektron 21. Heterogeneous strain fields are obtained from localized deformation in the microstructure. The objective of this work is to correlate the locations of fatigue crack initiation and fatigue crack growth with intergranular strains and the distribution of microstructural features such as brittle intermetallic phases.